Unplug! world wider than WWW : a campaign addressing internet dependency amongst youth in Singapore - Chew, Wen Jing (2012)
In recent years, Internet Dependency has been recognised as a growing problem in many countries. However, there seemed to be a lack of concrete programmes addressing the issue amongst tertiary students in Singapore. Considering that Singapore is one of the most highly wired countries in the world, the prevalence of an excessive dependence on the Internet poses a significant threat to the physical and psychological well-being of local youth. This convinced four undergraduates to embark on a campaign, titled Unplug!, to raise awareness about Internet Dependency and the importance of moderating one’s time online.Built on the concepts of self-evaluation and peer influence, Unplug! followed a strategic three-step process to reach out to undergraduates in Singapore. Interactive programmes, interesting collaterals and a consistent media presence were utilised to encourage youth to embrace a world wider than the World Wide Web.